1968
DOI: 10.1136/bmj.4.5629.477
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Rhesus Immunization. A Controlled Clinical Trial with a Comparatively Low Dose of Anti-D Immunoglobulin

Abstract: Summary: A controlled clinical trial was carried out to test the effectiveness of a comparatively low dose of anti-D immunoglobulin (250 pg) in preventing rhesus immunization.In the control group 17 out of 329 women (5%) formed rhesus antibodies, whereas in the treated group only 3 out of 333 women (0.9%) showed active immunization, all three of whom had an exceptionally large transplacental bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Most trials were performed in the 1960’s and 1970’s [ 30 , 33 – 39 ], and several had multiple publications providing data at different time points or from different countries (footnoted in Table 2 ). Six trials evaluated postpartum RhIg [ 30 , 33 – 35 , 38 , 40 ], three trials evaluated antenatal RhIg [ 32 , 41 , 42 ], two trials evaluated RhIg given to women who experienced abortion [ 37 , 39 ], and two trials evaluated antenatal RhIg given either intramuscularly or intravenously [ 43 , 44 ]. All but one trial [ 42 ] reported the women who were sensitized within the first year postpartum or at a subsequent Rh-positive pregnancy, and four studies reported adverse events (AEs) [ 39 , 42 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most trials were performed in the 1960’s and 1970’s [ 30 , 33 – 39 ], and several had multiple publications providing data at different time points or from different countries (footnoted in Table 2 ). Six trials evaluated postpartum RhIg [ 30 , 33 – 35 , 38 , 40 ], three trials evaluated antenatal RhIg [ 32 , 41 , 42 ], two trials evaluated RhIg given to women who experienced abortion [ 37 , 39 ], and two trials evaluated antenatal RhIg given either intramuscularly or intravenously [ 43 , 44 ]. All but one trial [ 42 ] reported the women who were sensitized within the first year postpartum or at a subsequent Rh-positive pregnancy, and four studies reported adverse events (AEs) [ 39 , 42 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…In RCTs, RoB was moderate and high for sensitization and high for AEs ( Table 4 ). Four studies did not use truly random methods for randomization (e.g., birth date) [ 30 , 34 , 35 , 41 ] and six studies did not provide sufficient information to judge the method of randomization [ 32 , 33 , 38 , 39 , 42 , 43 ]. The method of allocation concealment was not reported in seven of the trials [ 32 , 33 , 38 – 40 , 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations